Functioning and development of social infrastructure of rural areas - Spanova , B.K. (BUKETOV BUSINESS REVIEW, 2018)
The article emphasizes that the development of market mechanisms involved in its orbit not only the traditional industries of material production, but also the social infrastructure, its components: education, health, culture, housing and communal services, transport and communications for serving the population. In this regard, the growing importance of social development factors is becoming increasingly important, and this raises the need for research related to the improvement of the social infrastructure in the countryside. Based on the analysis of the activities of the state program on social development of the village, the tendencies of strengthening the infrastructural potential of rural areas, its relationship with increasing the attractiveness for the population and the investment attractiveness of the agrarian economy were investigated. The conclusion is made about the effectiveness of state measures for the development of rural areas and the need to strengthen them to create comfortable living conditions for the population. The opinion is shared that it is required to significantly increase the scale of state support to the village, first of all, to solve the problem of providing the population with housing, education as the basis for creating a competitive reproduction of social infrastructure. On the basis of statistical data, it was concluded that one of the main problems of the social sphere is the discrepancy between the social guarantees of the state and the financing of the social sphere aimed at the implementation of state guarantees, and therefore the involvement of state bodies in solving large-scale social problems is required.